An Inclusive Local Irregularity Vertex Coloring of Dutch Windmill Graph - Kristiana, Arika Indah; Prahastiwi, Lusi Rizzami; Prihandini, Rafiantika Megahnia (CAUCHY: Jurnal Matematika Murni dan Aplikasi, 2023)
Let G(V,E) is a simple and connected graph with V(G) as vertex set and E(G) as edge set. An inclusive local irregularity vertex coloring is a development of the topic of local irregularity vertex coloring. An inclusive local irregularity vertex coloring is defined by coloring the graph so that its weight value is obtained by adding up the labels of the neighboring vertex and its label. The inclusive local irregularity chromatic number is defined as the minimum number of colors obtained from coloring the vertex of the inclusive local irregularity in graph G. In this paper, we find the inclusive local irregularity vertex coloring and determine the chromatic number on the Dutch windmill graph using axiomatic deductive and pattern recognition methods. The results of this study are expected to be used as a basis for studies in the development of knowledge related to the inclusive local irregularity vertex coloring